Inheritance of cold stress tolerance in grapes - Esensee, Virgil D., author; Hughes, Harrison G., advisor; Johnson, Duane, committee member; Lee, Chi Won, committee member; Towill, Leigh E., committee member (Colorado State University. Libraries, 1989)
Cold hardy 'Valiant' was crossed to the lesser hardy cultivars 'Zinfandel' and 'French Colombard' to produce progeny that were later planted in the field for evaluation. In January and February, 1989, buds with subjacent stem tissue were evaluated by differential thermal analysis (DTA). The results were compared with those obtained from tests of browning that were performed following controlled freezing of buds in a methanol bath. DTA was found to be an accurate means to determine the mean midwinter killing temperature of grape buds. The apparatus used cooled the experimental tissues at a smooth linear rate (-15.8 C/hr) and produced low variances within replicates. An analysis of variance indicated that there were true differences between progeny means. Field evaluations in June, 1989, also verified the midwinter DTA data. These tests substantiate recommending DTA as a breeding tool for evaluating midwinter grape cold hardiness. Broad sense heritability was calculated using grape bud DTA data for both 'Valiant'x'Zinfandel' and 'Valiant'x'French Colombard' crosses. All calculations produced heritabilities near unity, indicating that of the progeny tested, the phenotypes were due primarily to expression of the genotypes. It was also found that poor seed germination commonly found in grapes can be ameliorated through the use of embryo rescue techniques. Data showed that low germination of grape seeds is not necessarily due to inviability, since rescued embryos grew and developed when placed on Nitsch's medium.
Covers not scanned.
Keywords: Grapes